2011
DOI: 10.1002/hep.24692
|View full text |Cite
|
Sign up to set email alerts
|

A Human monoclonal antibody targeting scavenger receptor class B type I precludes hepatitis C virus infection and viral spread in vitro and in vivo

Abstract: End-stage liver disease caused by chronic hepatitis C virus (HCV) infection is the leading indication for liver transplantation in the Western world. However, immediate re-infection of the grafted donor liver by circulating virus is inevitable and progresses much faster than the original disease. Standard antiviral therapy is not well tolerated and usually ineffective in liver transplant patients while anti-HCV immunotherapy is hampered by the extreme genetic diversity of the virus and its ability to spread vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 56 publications
(98 reference statements)
0
100
2
Order By: Relevance
“…So far small molecules and mAbs targeting SR-BI and interfering with HCV infection have been described (Bartosch et al 2003;Catanese et al 2007;Syder et al 2011). A codon-optimized version of this mAb has been demonstrated to prevent HCV spread in vivo (Meuleman et al 2012), and ITX5061, a SR-BI inhibitor, is in clinical development as HCV entry inhibitor (phase I, http:// clinicaltrials.gov/ct2/show/NCT01560468?term¼ITX+5061&rank¼3).…”
Section: Hcv Infectionmentioning
confidence: 99%
“…So far small molecules and mAbs targeting SR-BI and interfering with HCV infection have been described (Bartosch et al 2003;Catanese et al 2007;Syder et al 2011). A codon-optimized version of this mAb has been demonstrated to prevent HCV spread in vivo (Meuleman et al 2012), and ITX5061, a SR-BI inhibitor, is in clinical development as HCV entry inhibitor (phase I, http:// clinicaltrials.gov/ct2/show/NCT01560468?term¼ITX+5061&rank¼3).…”
Section: Hcv Infectionmentioning
confidence: 99%
“…[85] (see Table 1) is particularly amenable to investigate cell-to-cell transmission [85,102,188] as it allows at the same time distinguishing two different cell populations (producer and target cells) and tracking rare infection events at the single cell level. As an alternative to using two cell populations, counting the number of cells per infection focus after culture under an agarose overlay has been used as an estimate of cell-to-cell transmission efficiency [171,189].…”
Section: Cell-to-cell Transmissionmentioning
confidence: 99%
“…We also investigated whether the CLDN-1 antibodies B9X and D10X could synergize with the anti-SRB1 antibody C-1671, which potently inhibits infection and spread in vivo in the human liver-chimeric mouse model (Meuleman et al, 2012). Combination of C-1671 with D10X resulted in measurable synergy when tested against four virus strains, including two clinically derived isolates.…”
Section: Discussionmentioning
confidence: 99%
“…mAbs against CD81 and SRB1 have been shown to inhibit HCV infection in vitro and in vivo. In particular, we previously showed that the human anti-SRB1 mAb C-1671 completely prevents infection and intrahepatic spread of multiple HCV genotypes in vivo in human liver-chimeric mice (Meuleman et al, 2012). Human mAbs against CLDN-1 and OCLN have not been reported yet, but rat, mouse and mouse/human chimeric anti-CLDN-1 antibodies were found to efficiently inhibit infection by HCV of major genotypes in cell culture (Fofana et al, 2010;Yamashita et al, 2015) and some of them eliminate chronic HCV infection without detectable toxicity when administered to human liver-chimeric mice Mailly et al, 2015).…”
Section: Introductionmentioning
confidence: 99%